Childhood Character Building in Drama Script Mencari Taman by Noorca M. Massardi : A Literary Psychology Approach - Najma Murdhia; Wika Soviana Devi (DISASTRA: PENDIDIKAN BAHASA DAN SASTRA INDONESIA, 2022)
Character building in children is important to help them have good characteristics and personalities. The characteristics of each child are also important and must be understood by parents to educate their children well. The purpose of this study was to describe the character building in children in the drama script "Mencari Taman." The study of the drama script entitled "Mencari Taman" applied a Literary Psychology approach, namely through understanding the psychological theory used to analyze a literary work and examining the formation of characters in the play. This research employed the content analysis method. This research is literary research through the analysis of data collected by document review and analysis. Based on the results of the analysis, several values shaping the characteristics of children were found in the drama script "Mencari Taman" by Noorca M. Massardi, and they were the values of discipline, humanity, concern for the environment, compassion, religion, and noble character..